MODEL PEMBELAJARAN BERBASIS PROYEK (PROJECT BASED LEARNING) TERHADAP KEMAMPUAN MEMBUAT SUSU KEDELAI ANAK TUNANETRA - CHOIRUN NISA, HAFSAH (Jurnal Pendidikan Khusus, 2016)
ABSTRACT The ability to make soybean milk is an individual’s ability in doing soybean processing products. It is not only able for consumption but also for prospective business. It is not easy to train students with visual impairment to be independent. Being, independent, it is expected that students with visual impairment develop their knowledge and skills in social life. Student with visual impairment is an individual whose eyesight is not normally functioning receiver in daily activities as on normal people do. In giving assignment to make soybean milk, teacher must apply a learning model that suits the needs and conditions of these students. In this case, an interesting, varied and concrete learning strategy is needed to facility students’ learning. The purpose of this study is to examine the ability of students with visual impairment to make soybean milk before and after the get intervemtions using Project Based Learning. The pre-experimental approach was applied in this research. The researchs spent eight meetings with six times interventions. The research design was one group pretest posttest design, seven students were selected as the research sample. The data collection techniques were test, observation, and documentation. The data analysis techniques was non-parametric statistics using sign test. The analysis showed that there was improvement in the scores of students with visual impairment from the pretest score 52,86, to the post test score 85,00. The result of the study which were analyzed by using sign test formula obtained Zobserved (Zh) = 2.27, while the Ztable with 5% significance for two-sided test is 1.96. Therefore, Ho was rejected and Ha was accepted proven by (1.96 <2.27> 1.96). Based on these data, it can be concluded tha the Project Based Learning Model (Project Based Learning) affected the students with visual impairment ability to make soybean milk in SMPLB-A YPAB Surabaya.   Keywords: Project Based Learning, the ability to make soybean milk